The contextualization of professi o nal training of the f uture fashion designers in higher education al inst itutions (Pedagogy of Higher and Secondary Education, 2016)
Zhelanova V. V. The contextualization of professional training of the future fashion designersin higher educational institutions.In the article the problem of specialists training in design sphere in higher educational institutions is substantiated. The Modern Discourse Studies of contextualization of professional training problems is indicated. The essence of the contextualization phenomenon is analyzed as a basic principle of modern education. The principle of contextualization is represented in formate of the professional training of fashion designers at universities. The conceptual principles of contextualization of professional training of future fashion designers are shown. The concepts «contextual approach», «context», «professional context» are defined. The phenomenon «professional context of the future fashion designer» and its structure are grounded. The professional context of the future fashion designer is represented by complex of motives, installations, value relations for the process and outcome of clothes designing. It was found that motivational-value context reflects the incentive aspects of professional work of fashion designer. It is associated with personal interest, desire, propensity to engage in apparel design, an approach to the labor itself as a value. It is a set of motives, attitudes, values, relationship to the process and  utcome of designing clothes. Creative and projecting context reflects the stage of designing clothes, namely: pre-search related to the analytical work (analysis of consumer needs, his anthropometric data, diagnosis of  sychological personality traits, analysis of manufacturing of technical and economic requirements), the image  designing (includes shaping and development of color palette) production context associated with the productionof clothing technology (process context) and communication subjects in this process (the communicative context). The conceptual scope of contextualization is solved. The organizational aspects of contexstualization related using definitely teaching tool are represented. The teaching tool is provided by imitative and not imitative forms of organizational learning.
Keywords: contextual approach; contextualization; context; profess i onal context of the future fashion designer; motivational - value context; creative - projecting context; pro ductional context